Lemus López, Encarnación. Ellas. Las estudiantes de la Residencia de Señoritas. Madrid, Cátedra, 2022. - Núñez Nadal, Carmen (CIAN-Revista de Historia de las Universidades, 2024)
Este artículo reseña: Lemus López, Encarnación. Ellas. Las estudiantes de la Residencia de Señoritas. Madrid, Cátedra, 2022.